Mobile internet, skills and structural transformation in Rwanda - Bernardo Caldarola; Marco Grazzi; Martina Occelli; Marco Sanfilippo (International Labour Organization (ILO), 2022)
This paper examines the relationship between mobile internet, employment and structural transformation in Rwanda. Thanks to its ability to enable access to a wide range of ICT technologies, internet coverage has the potential to affect the dynamics and the composition of employment significantly. To demonstrate this, we have combined GSMA network coverage maps with individual-level information from national population censuses and labour force surveys, creating a district-level dataset of Rwanda that covers the period 2002 to 2019. Our results show that an increase in mobile internet coverage affects the labour market in two ways. First, by increasing employment opportunities. Second, by contributing to changes in the composition of the labour market. Education, migration and shifts in demand are all instrumental in explaining our findings.
Keywords: 330; labour economics; employment; migrant workers; skilled workers; unskilled workers; skills; economic and social development; information and communication technologies; intermediate technology; technological change